Bridging Experiential Learning and Spiritual Wisdom: Integrating Kolb’s Cycle with the Four Noble Truths of Buddhism - Marikar, Faiz; Kodithuwakku, Malake (Educational Challenges, 2024)
Purpose. This study aims to explore the potential integration of Kolb’s Experiential Learning Cycle with the Four Noble Truths of Buddhism to offer a comprehensive framework for personal growth and transformation. Methodology. A qualitative analysis was conducted, drawing on existing literature on Kolb’s learning theory and Buddhist philosophy. The study focused on identifying parallels and synergies between Kolb’s four-stage learning cycle and the Four Noble Truths, elucidating how their integration could enhance understanding and application of spiritual principles in daily life. Results. The analysis revealed significant alignment between Kolb’s cycle and the Four Noble Truths. Reflective observation corresponds to the acknowledgment of suffering (First Noble Truth), the identification of its causes (Second Noble Truth). Abstract conceptualization mirrors the understanding of the cessation of suffering (Third Noble Truth) through wisdom and insight into the nature of existence. Active experimentation resonates with the Noble Eightfold Path (Fourth Noble Truth), emphasizing the practical application of ethical conduct, mental cultivation, and wisdom development to alleviate suffering. The integration of Kolb’s Experiential Learning Cycle with the Four Noble Truths offers a holistic approach to personal growth and transformation. By combining experiential learning with spiritual wisdom, individuals gain a deeper understanding of the causes of suffering and the path to liberation. This integrated framework provides a structured methodology for cultivating resilience, wisdom, and compassion in daily life, fostering holistic development and contributing to greater well-being and fulfillment. Conclusion. Further research and practical application of this framework holds promise for enhancing individual and collective flourishing in diverse cultural and educational contexts.